Health Determinants - Alnaqbi , Shaikha (Global Journal of Health Sciences, 2023)
Purpose This study focuses on three major healthy people UAE domains aiming to investigate key health issues, including context, current burden, problems, domain development, and challenges. It outlines an objective for addressing health issue determinants, defines attainable goals, and establishes indicators for progress measurement. Methodology In order to collect data and analyze the interpretations of the current burden, we conducted a literature review using previous studies, analyzed the variables and factors to address the problem, and finally set goals and indicators aiming to achieve the targets. Findings Previous studies have demonstrated the significance of lifestyle-related diseases, life expectancy, health care services, health domains, and their challenges. Still, they lack initiatives and indicators for measuring the health outcome's progress. In this paper, we discuss goals that can be achieved and indicators that can be used to track development toward a more desirable state for the UAE population.